ANALISIS KONSEP DIRI SISWA KELAS XI IPS SMA N 1 BENAI TAHUN AJARAN 2015/2016 - A Alfi Qadri A Alfi Qadri; Tri umari Tri umari; Rosmawati Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : The school year is a time to achieve self-identity in which students explore themselves by interacting and socializing with peers , by actively participating in the activities of peers, to be honest , responsible and follow the rules or norms adopted by a group of peer. This study aims 1) To determine the overall picture of the self concept of students of class XI IPS , 2) To know the self-concept of students by gender , 3) To know the self-concept of student by items. This study use the method of data collection and the data anailyze. The subjects of this study were students of class XI IPS SMA N 1 Benai were 52 student. Determining samples using Saturated samples and samples in this study were 52 student. The scale of self-concept in this study using Goleman scale. This test totaled 30 items that consists of 15 ( + ) and 15 ( - ) . Positive statements that answered yes were given a score 1 (one) , and the answered no were given a score of 0 (zero),otherwise negative statement that answered yes will be given a score 0 (zero), and the answers were not given a score 1(one ). Based on the results of research which conducted it can be concluded that after conducted of data analysis of the self-concept and we know description of self-concept of class XI IPS SMA N 1 Benai was 65.34 % for good and 34.61% for good enough.Key Word : Analysis of Self Concept.